PENGARUH HARGA, FASILITAS, PENGELUARAN KONSUMEN, DAN ANGGOTA JUMLAH KELUARGA TERHADAP PERMINTAAN RUMAH KPR BERSUBSIDI KECAMATAN ALALAK KABUPATEN BATOLA - Jumriyanor Jumriyanor; Rusdianysah Rusdianysah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
The research was conducted to find out: 1. How the price, facilities, consumer spending, and number of households had on subsidized home demand. 2. Which factor is most dominant affecting the demand of subsidized home MORTGAGES. This method of research uses quantitative and qualitative approaches. Variables or factors affecting the demand for a home that can be translated in numbers, will be analyzed with a quantitative approach, but information from consumers that cannot be translated in numbers will be depicted In the form of a qualitative narrative.The results showed that the facility factor, consumer spending was influential on the demand for subsidized homes in the district Alalak Barito Kuala District, stated that the most influential factor is the consumer spending factor With a result of the calculated T 2,453 and the second is the facility factor with a result of the count of 2,082. Simultaneously the whole of variables X1, X2, X3, X4. Effect on the Y of the test results F, F count of 4,302. means the price, facilities, consumer spending, the number of simultaneous families have a positive effect on the demand of subsidized homes in the sub-district of Batola district.Keywords: price factors, facilities, consumer spending, number of families, to home demand